2021
DOI: 10.1029/2020ja029081
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Event Analysis of Plasma and Field Variations in Source of Stable Auroral Red (SAR) Arcs in Inner Magnetosphere During Non‐Storm‐Time Substorms

Abstract: Stable auroral red (SAR) arcs are optical events with dominant 630.0-nm emission caused by low-energy electron heat flux into the topside ionosphere from the inner magnetosphere. SAR arcs are observed at subauroral latitudes and often occur during the recovery phase of magnetic storms and substorms. Past studies concluded that these low-energy electrons were generated in the spatial overlap region between the outer plasmasphere and ring-current ions and suggested that Coulomb collisions between plasmaspheric e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 84 publications
2
11
0
Order By: Relevance
“…It has been known that other types of detached auroral arcs, such as SAR (stable auroral red) arcs (e.g., Hong et al., 2020; Inaba et al., 2020, 2021) and STEVE (Strong Thermal Emission Velocity Enhancement) (e.g., Archer et al., 2019) are accompanied by ionospheric irregularities with local density enhancements (SAR arc) and depletions (STEVE) in the auroral regions. Our study also showed that an IPA event is accompanied by localized plasma density enhancements in the plasma trough.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known that other types of detached auroral arcs, such as SAR (stable auroral red) arcs (e.g., Hong et al., 2020; Inaba et al., 2020, 2021) and STEVE (Strong Thermal Emission Velocity Enhancement) (e.g., Archer et al., 2019) are accompanied by ionospheric irregularities with local density enhancements (SAR arc) and depletions (STEVE) in the auroral regions. Our study also showed that an IPA event is accompanied by localized plasma density enhancements in the plasma trough.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known that other types of detached auroral arcs, such as SAR (stable auroral red) arcs (e.g., Hong et al, 2020;Inaba et al, 2020Inaba et al, , 2021 and STEVE (Strong Thermal Emission Velocity Enhancement)…”
Section: Discussionmentioning
confidence: 99%
“…Proton aurora is caused by energetic ions that are scattered by electromagnetic ion cyclotron waves and precipitate to the upper atmosphere. Energetic ions also heat ambient cold plasma (plasmasphere), and heated thermal electrons are believed to cause SAR arcs (Inaba et al., 2021). Proton aurora occurs near the meridian of intensifications in the auroral oval (streamers) (Henderson, 2021; Montbriand, 1971; Nishimura et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The detected density fluctuations categorized in the MLT‐dependent plasmasphere near the apogee may be caused by the satellite “skimming” along the plasmapause rather than actual density irregularities (e.g., Figure 8 of Inaba et al. [2021]). To resolve these problems, we used L − L pp to measure the distance between the satellite and the PBL.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the large and frequent density fluctuations in the PBL, it must be investigated whether the density irregularities in the plasmasphere and plasma trough are associated with the PBL. The detected density fluctuations categorized in the MLT-dependent plasmasphere near the apogee may be caused by the satellite "skimming" along the plasmapause rather than actual density irregularities (e.g., Figure 8 of Inaba et al [2021]). To resolve these problems, we used L − L pp to measure the distance between the satellite and the PBL.…”
Section: Resultsmentioning
confidence: 99%